An ode to a autoethnography / Rofiza Aboo Bakar - Aboo Bakar, Rofiza (Academy of Language Studies, 2023)
Autoethnography, a self-discovery journey, A process of reflection, a search for identity, Exploring the self, through stories we tell, Weaving together past and present, to create a tale. Autoethnography allows us to see, The intersection of our lived experiences and society, We reflect on our biases, and question what we know, To understand our pursuit in the world and how we grow. Through this method, we unearth our past, And delve into the moments we want to last, We uncover the memories that shape who we are, And dissect the culture that surrounds us, near and far. Through this process, we unite with others, Sharing our stories, discovering our brothers and sisters, Learning from one another, and find common ground, As we navigate the complexities that life can bring around. Thus, let us embrace autoethnography, To tell our stories, to search for our identities, To gain new perspectives, and connect with humanity, As we journey through life's odyssey,